Assessing the Translation of Research and Innovation into Dental Practice. (July 2020) - Heft, M.W.; Fox, C.H.; Duncan, R.P.
Introduction: Over the past 100 y, there have been an unprecedented number of innovations that have improved oral health and functioning. Variations in lag times between discovery and clinical adoption are related to dentist education, the clinical availability of technology, and the perceived value of an innovation. Objectives: The purposes of this cross-sectional study were 1) catalogue research discoveries and innovations over the past 30 y and 2) from that list identify those which practicing dentists believe have maximally affected patient care. Methods: Thirty International Association for Dental Research leaders identified innovations over the past 30 y that have significantly affected dental care. The 30 most cited innovations were included in a questionnaire that was sent to a random sample of US dentists who graduated dental school during or before 1995 (before the recency of identified discoveries) and devoted ≥50% of their time to patient care. Eighty-two percent of respondents identified as general dentists and 18% as specialists. Respondents were asked to identify 5 to 7 items whose loss would have the most adverse effects on patient care. Results: The most cited advances were adhesive dental materials (74.5%), dental implants (71.9%), direct bonding systems (71.2%), dental loupes (54.7%), universal precautions for infection control (48.6%), and digital imaging (46.0%). There were differences in the ranking of responses between generalists and specialists. For the oral surgeons and periodontists (OMSPER, n = 51), top choices were dental implants (82%), cone beam computed tomography (CBCT) imaging (74%), regenerative dentistry and tissue engineering (68%), universal precautions (58%), digital imaging (56%), and dental loupes (48%). Conclusions: There was agreement among generalists and specialists about the importance of dental implants, digital imaging, use of dental loupes, and universal precautions in improving patient care. However, generalists also cited the importance of adhesive dental materials and bonding, and OMSPER cited CBCT and biological-based tissue restoration as major advances. Knowledge Transfer Statement: Many advances in dental patient care capitalize on innovations and technologies that have emerged after dentists graduate from dental school. Adoption of new technologies is influenced by information acquired from professional journals, continuing education, industry marketing activities, and interactions with colleagues. The results of this study suggest that innovations that are directly related to clinical procedures were rated most impactful. Future research should consider cost-effectiveness and patient perceptions on the impact of innovations and technologies.